Stakeholder Engagement in Instagram-Based Complaint Handling Indihome Service PT Telkom Yogyakarta Region - Haq, Mochammad Fauzul; Swastika, Septi Nur Hanna (CARAKA : Indonesia Journal of Communication, 2024)
This research aims to analyze Telkom Indonesia's engagement strategies with its stakeholders in Yogyakarta during a surge of complaints regarding their Indihome product on Instagram (@indihome.yogya). As a dominant internet service provider, Telkom Indonesia, through its Indihome product, faces a high volume of customer complaints, further amplified by the prevalence of social media platforms like Instagram, which provide a direct channel for customers to air their grievances. The study employs the Stakeholder Circle Model to examine the steps undertaken by Telkom Witel Yogyakarta in addressing customer complaints. A qualitative descriptive approach is adopted to gain a comprehensive understanding of the phenomenon under investigation. Data is gathered through interviews with key informants and a thorough examination of relevant documentation. The findings reveal that Telkom Witel Yogyakarta implements a five-stage stakeholder engagement process: (1) Identification: Creating a list of stakeholders; (2) Prioritization: Developing a stakeholder assessment scale; (3) Visualization: Conducting stakeholder mapping and dividing stakeholders into four quadrants; (4) Engagement: Implementing appropriate communication strategies tailored to each stakeholder category; (5) Monitoring: Evaluating the effectiveness of engagement efforts and ensuring alignment with expectations. This research contributes to the understanding of stakeholder engagement in complain handling from customers on social media platforms. The five-stage stakeholder engagement process offers a valuable framework for organizations seeking to improve their stakeholder relationships and effectively address customer concerns through social media channels.